SYNTHESIS OF NICKEL SULFATE FROM MIXED HYDROXIDE PRECIPITATE THROUGH SOLVENT EXTRACTION METHOD USING VERSATIC 10 AND CYANEX 272 EXTRACTANTS - Sondang Ariani Gultom, Giacinta
The usage of electric vehicles (EVs) is currently widespread in many countries, including Indonesia. This has led to a significant growth in the production of electric cars, consequently increasing the demand for nickel sulfate as one of the raw materials for lithium-ion battery cathodes in EVs. The production process of nickel sulfate from mixed hydroxide precipitate (MHP) generally consists of two main stages: MHP leaching with sulfuric acid and solvent extraction (SX). This research aims to study the SX process to separate nickel and cobalt from the rich leach solution of MHP using two different organic solutions, each containing Versatic 10 and Cyanex 272 extractants. The concentrations of Versatic 10 and Cyanex 272 used are 20% and 15% v/v respectively, with the addition of 5% v/v tributyl phosphate (TBP) and kerosene as a diluent. The experimental conditions for leaching and SX are based on previous research findings. The obtained solids are analyzed using X-ray diffraction (XRD), while the extracted solutions are analyzed using atomic absorption spectroscopy (AAS). The leaching operation conditions are as follows: solid concentration of 100 g/L, sulfuric acid concentration of 1.0 M, room temperature and pressure, and stirring for 3 hours. For the first SX experiment with Versatic 10, the experiment is conducted at an organic/aqueous (O/A) ratio of 0.5, temperature of 40°C, and pH equilibrium of 7.0. The stirring is carried out for 10 minutes at a stirring speed of 400 rpm. The sequential extraction percentages of nickel and cobalt obtained are 96% and 88% respectively, while magnesium extraction is 35%. Metal stripping is performed at a sulfuric acid concentration of 0.5 M with O/A = 1, temperature of 40°C for 10 minutes, resulting in a nickel recovery percentage of 64%. The extraction using Cyanex 272 for the separation of nickel and other metals is performed with a stirring time of 10 minutes, pH of 5.5, and the optimal ratio of O/A = 1, yielding a nickel recovery percentage of 99% in the aqueous phase and 83% for cobalt in the organic phase. Nickel and cobalt have been successfully separated.